Aspects of Accounting and Statistical Work of Local General Courts in Investigating the Cases on Administrative Offence - KULYNYCH, R.; HINCHUK, L. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2023)
article contains an analysis of the issue of accounting and statistical work of local general courts in investigating the cases of administrative offence. It was revealed that the statistical indicators measuring the number of investigated cases and persons charged responsible for the committed administrative offence specifi ed by the Code of Ukraine on Administrative Offences, or the offences not covered by this Code but included in other Laws of Ukraine characterized the real situation with committing administrative offence and the effectiveness of fight against this category of offence. The need for improvements in the statistical reporting on the observance of administrative law is substantiated. The study includes an analysis of the data on administrative offence in Ukraine in 2018, published on the official website of the State Statistics Service of Ukraine, and the reporting, in the established format, of the first instance courts on the investigation of cases on administrative offence. Selected indicators were analyzed, measuring the observance of the administrative law in Ukraine, the duration of the investigation of the cases on administrative offence by the first instance courts in comparison with the duration of legal proceedings in criminal, administrative and civil courts. Results of the analysis show that the share of cases on administrative offence, investigated in local general courts in 2021 and ended by the administrative prosecution, was only 49.4% of the total cases in legal proceeding. The conclusion is made that it is caused by a wide circle of circumstances ruling out legal proceedings in administrative courts, specified in the Ukrainian Code on Administrative Offences. Based on the analysis, proposals on the elimination of the revealed systemic problems are given, which can be useful in substantiating effective and timely measures for fighting against administrative offence.